Quality Assessment of Neonatal Transport performed by the Mobile Emergency Medical Services (SAMU) - Juliana C.F. Romanzeira; Silvia W. Sarinho (Elsevier, 2015)
Objective: To assess the quality of neonatal transport performed by the Mobile Emergency Medical Services (Serviço de Atendimento Móvel de Urgência [SAMU]). Methods: This was a cross-sectional before-and-after observational study. The study was carried out from March to August of 2013 using a validated instrument, the Transport Risk Index of Physiologic Stability (TRIPS), to assess the characteristics of the newborn, medical and mechanical complications (equipment and ambulance), and stability of newborns before and after transport. Tests were conducted with 95% confidence level. Numerical variables are represented by measures of central tendency and dispersion. Categorical variables were compared by Fisher's exact test. In the comparison of variables between the groups, the Student's t-test was used for variables with normal distribution, Fisher exact test, when appropriate, and the Mann-Whitney test, for non-normal distribution. Results: 33 newborns were transported from low-risk units to neonatal intensive care units. Male gender (57.6%) and full-term gestational age (63.6%) were more prevalent. Birth weight < 2,500 g was found in 39.4% of newborns. Respiratory failure accounted for 42.4% of the requests. The mean transport time was 58 minutes without medical or mechanical complications. The TRIPS score worsened in 15% of neonates; in this group of infants, the mean initial temperature of 36.46 ± 0.19 decreased significantly to 36.08 ± 0.22 (p = 0.041). Conclusion: The transport performed by the SAMU was adequate for most newborns. The oscillation in body temperature was the only significant variable for the alteration in the TRIPS score. Resumo: Objetivo: Verificar a qualidade do transporte neonatal realizado por serviço de atendimento móvel de urgência (SAMU). Métodos: Estudo observacional transversal de antes e depois, de março a agosto de 2013. Utilizou-se instrumento validado de avaliação do transporte, o Transport Risk Index of Phisiologic Stabilit (TRIPS). Foram analisadas características dos recém-nascidos, intercorrências de aspecto médico e mecânico (das máquinas e ambulância) e a estabilidade, antes e depois do transporte. Os testes foram aplicados com 95% de confiança. As variáveis numéricas estão representadas pelas medidas de tendência central e de dispersão. As variáveis categóricas foram avaliadas pelo Teste Exato de Fisher. Na comparação das variáveis entre os grupos utilizou-se o Teste T-Student para as distribuições normais, teste exato de Fisher, quando indicado, e de Mann-Whitney para as não-normais. Resultados: 33 recém-nascidos foram transportados de unidades de baixo risco para unidade de terapia intensiva neonatal. Prevaleceram o gênero masculino (57,6%) e a idade gestacional a termo (63,6%). Peso de nascimento abaixo de 2500 g foi encontrado em 39,4% dos recém-nascidos. Insuficiência respiratória foi responsável por 42,4% das solicitações. A duração média do transporte foi de 58 minutos, sem intercorrências médicas ou mecânicas. O escore Trips piorou em 15% dos pacientes e nesse grupo de RN, a média da temperatura inicial de 36,46 ±0,19 diminuiu de forma significativa para 36,08 ± 0,22 (p = 0,041). Conclusão: O transporte realizado pelo SAMU foi adequado para a maioria dos recém-nascidos. A oscilação da temperatura corporal foi a única variável importante para alteração do escore no transporte. Keywords: Transport services, Newborn, Emergency Medical Services, Palavras-chave: Serviços de Transporte, Recém-nascido, Serviços Médicos de Emergência